Using Narrow Band CE-Chirps to Elicit Cervical Vestibular Evoked Myogenic Potentials. Issue 3 (1st May 2022) - Mat, Quentin; Deggouj, Naïma; Duterme, Jean-Pierre; Tainmont, Sophie; Lelubre, Christophe; Manto, Mario
Abstract : Objectives: To compare the effects of Narrow band CE-Chirps (NB CE-Chirps) and tone bursts (TBs) at 500 Hz and 1000 Hz on the amplitudes and latencies in cervical vestibular evoked myogenic potentials (cVEMPs). Design: Thirty-one healthy adult volunteers of varying ages were tested by air conduction at 95 dB nHL. Recording conditions were randomized for each participant and each modality was tested twice. Results: NB CE-Chirps showed larger corrected amplitudes than TBs at 500 Hz ( p < 0.001) which were themselves larger than NB CE-Chirps and TBs at 1000 Hz ( p < 0.001). In older volunteers, NB CE-Chirps 500 and 1000 Hz had significantly higher response rates than TBs 500 Hz ( p = 0.039). A negative correlation was observed between the corrected amplitudes and the age of the participants regardless of the stimulus and the frequency studied. The p13 and n23 latencies were not correlated with the age of the subjects. Conclusions: NB CE-Chirps at 500 Hz improved the corrected amplitudes of waveforms in cVEMPs as a result of a better frequency specificity compared with TBs. In the elderly, eliciting cVEMPs at a frequency of 1000 Hz might not be necessary to improve response rates with NB CE-Chirps. Additional studies including a higher number of healthy participants and patients with vestibular disorders are required to confirm these observations.